Implementation of Formal English Use in Direct Communication Contexts - Morada Tetty; Avta Nia Lestari; Vauline Mikha Sherly Angel; Rahel Vincentia J Sianipar; Vera Ester Enjellina; Sriwi Anceli Naibaho; May Devi Triana (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
This study examines the implementation of formal English in direct communication among high school students, focusing on both verbal (vocabulary, sentence structure) and nonverbal (intonation, gestures) aspects. Using a quantitative descriptive method with 28 eleventh-grade students at a private high school, the research employed a three-phase design: (1) diagnostic pre-test,where students filled out a language background questionnaire and completed a short individual presentation to assess their initial formal English use; (2) structured training intervention, which included direct instruction on formal sentence patterns, academic vocabulary, and appropriate tone, followed by guided practice through simulated speaking tasks; and (3) presentation-based post-test, in which students gave individual presentations in groups, and their verbal and nonverbal performance was assessed using rubrics and observation checklists. The analysis focused on students’ awareness of language register in formal contexts, supported by communicative-based instruction emphasizing real-life academic language use. Results revealed that while 78.5% of students initially struggled to distinguish formal from informal registers, the intervention significantly improved informal-to-formal sentence transformation (80% accuracy) and academic vocabulary usage (+40%). Persistent challenges emerged in nonverbal elements, including inconsistent eye contact (65% of students) and flat intonation (45%). The study demonstrates the efficacy of explicit instruction and recommends integrating structured nonverbal training into language curricula through targeted classroom activities.